4 - A la recherche d’un primitivisme fédérateur : le peintre Atlan et le groupe Cobra - Anissa Bouayed, (Afrika Zamani, 2022)
When young Jean-Michel Atlan left his hometown of Constantine in 1930 at the age of eighteen, he left Algeria to read philosophy at the Sorbonne University in Paris. His love for poetry drove him into artists’ circles of Montparnasse. As an anti-colonial activist and member of the Resistance Movement, he entirely indulged into painting since the start of the Liberation. He enjoyed an instant success in Paris and soon became internationally acclaimed. Atlan claims to be a Berber-Jew while denying assignments with colonial overtones. It is an art with «barbaric» or «primitive» trends. A few years later, the Cobra roup took up the concept of «primitivism». This approach to cultural history seeks to capture how Atlan barged into the arts milieu and the encounter between Atlan and Cobra shows on the one hand common affinities, and the echoes of this concept in the field of contemporary art on the other hand.